Competency Determinants of Hotel Manager Effectiveness in a Wildlife Tourism Context: Insights from Jim Corbett National Park (International Journal of Environmental Sciences, 2024)
Efficient hotel administration in wildlife tourism locales necessitates skills that cater to both operational requirements and ecological awareness. This study analyses the managerial competences of hotel managers in star-rated establishments situated in Jim Corbett National Park, Uttarakhand. Utilising the hospitality competence framework established by Bharwani and Talib (2017) and augmented with Environmental Behaviour skills (Carlisle et al., 2022), the study assesses five domains: Cognitive, Functional, Social, Meta, and Environmental Behaviour skills. Data were gathered by a standardised questionnaire distributed to 190 managers from 14 hotels and examined utilising descriptive statistics and Cronbach’s Alpha reliability assessment. Research reveals that Meta Competencies—particularly self-awareness, self-efficacy, and achievement orientation—are the most prominent traits exhibited by managers. Cognitive competencies pertaining to decision-making, analytical reasoning, and problem-solving also receive elevated scores. Functional and social competencies are somewhat robust, especially in resource utilisation, communication, conflict resolution, and team collaboration. Environmental Behaviour Competencies demonstrate adequate engagement; still, enhancements are necessary in energy and water efficiency measures. The study finds Meta Competencies as the primary competency domain among managers in the context of wildlife tourism.A competency model designed for managers in protected tourism locations is offered, highlighting the amalgamation of ecological responsibility with conventional managing skills. The research provides insights for training, human resource development, and sustainable hospitality management in ecologically sensitive regions.